Framework of Inventory and Sales Information System at UD. PAPILON TERARA - Nukman Nukman; Yuan Sa’adati; Muhip Abdul Majid (PT. GWEX NET PUBLISHER, 2026)
In the administration section, it is often overwhelmed when there are so many sales orders, because the work is still done manually. Not to mention if the leadership wants reports quickly. The administration section must open and search for the archives related to the report to be made. This work takes up a lot of time, resulting in delays in the reports that will be given to the leadership. Based on these problems, the researchers took the initiative to create and implement a new application system. The framework that will be designed will make it easier for the administration in managing goods data or incoming and outgoing sales data because the database for storing data uses a MySQL database and the system is made using Visual Basic Net version 17.5. With this system is expected to overcome the problems mentioned above in order to help facilitate the working mechanism. Because the processing of inventory and sales data at UD. PAPILON Terara still uses conventional methods